2002
DOI: 10.1016/s0002-9610(02)01173-x
|View full text |Cite
|
Sign up to set email alerts
|

Medical and surgical options in the treatment of severe obesity

Abstract: Weight loss programs, diets, and drug therapy have not shown long-term effectiveness in treating morbid obesity. A 1992 statement from the National Institutes of Health Consensus Development Conference affirmed the superiority of surgical over nonsurgical approaches to this condition. Bariatric surgical procedures work in 1 of 2 ways: by restricting a patient's ability to eat (restrictive procedures) or by interfering with ingested nutrient absorption (malabsorptive procedures). Many of these procedures can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
158
1
29

Year Published

2004
2004
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(190 citation statements)
references
References 59 publications
2
158
1
29
Order By: Relevance
“…They can be divided into two general categories: restrictive procedures (i.e., adjustable gastric banding and sleeve gastrectomy) and malabsorptive procedures with or without restrictive components (i.e., biliopancreatic diversion, duodenal switch and Roux-Y-gastric bypass. 8 ) The efficacy and safety profiles among these categories vary substantially as a result of differences in the anatomic configurations produced and the alterations in gastrointestinal physiology that are created by the different surgical procedures. Whichever method is used, numerous short-and medium-term studies have confirmed that bariatric surgery is superior to conventional, non-operative methods in inducing weight loss and resolving comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…They can be divided into two general categories: restrictive procedures (i.e., adjustable gastric banding and sleeve gastrectomy) and malabsorptive procedures with or without restrictive components (i.e., biliopancreatic diversion, duodenal switch and Roux-Y-gastric bypass. 8 ) The efficacy and safety profiles among these categories vary substantially as a result of differences in the anatomic configurations produced and the alterations in gastrointestinal physiology that are created by the different surgical procedures. Whichever method is used, numerous short-and medium-term studies have confirmed that bariatric surgery is superior to conventional, non-operative methods in inducing weight loss and resolving comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…2 Nonsurgical management of obesity includes dietary changes and exercise, which can facilitate a 5%-10% weight loss. [3][4][5] Unfortunately, once patients stop a weight loss program, weight gain typically occurs.…”
mentioning
confidence: 99%
“…Some, but not all, studies show that obesity lowers wages [26,27]. In terms of productivity, recent papers have shown that the cost of obesity among full-time employees is highly concentrated among those eligible for bariatric surgery, which is only one-third of the obese population; that there is increased work loss by the patients who are surgically ineligible; and that in less than 4 years, bariatric surgery yields a net economic gain.…”
Section: Benefits Of Surgery To Workers and Insurersmentioning
confidence: 99%